The Effect of Carbon Accounting Disclosure, Environmental Performance, and CEO Characteristics on Financial Performance: The Role of Firm Size as a Control Variabel - Juniarti, Eva; Sasanti, Elin Erlina (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the effect of carbon accounting disclosure, environmental performance, and CEO characteristics (education, tenure, and gender) on the financial performance of energy sector entities recorded on the Indonesia Stock Exchange from 2021 to 2023, with firm size as a control variable. Using secondary data and panel data regression analysis processed with Stata 17, the findings reveal that only CEO gender significantly influences financial performance, albeit negatively. Other variables, including carbon accounting disclosure, environmental performance, CEO education, CEO tenure, and firm size, show no significant effects. These results highlight the complexity of financial performance determinants, emphasizing the need for improved carbon disclosure quality and long-term environmental strategies.